2005
DOI: 10.4141/p03-168
|View full text |Cite
|
Sign up to set email alerts
|

On-farm production and utilization of arbuscular mycorrhizal fungus inoculum

Abstract: . 2005. On-farm production and utilization of arbuscular mycorrhizal fungus inoculum. Can. J. Plant Sci. 85: 15-21. Arbuscular mycorrhizal (AM) fungi colonize the roots of the majority of crop plants, forming a symbiosis that potentially enhances nutrient uptake, pest resistance, water relations, and soil aggregation. Inoculation with effective isolates of AM fungi is one way of ensuring the potential benefits of the symbiosis for plant production. Although inocula are available commercially, on-farm productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 27 publications
1
49
0
1
Order By: Relevance
“…The beneficial effects of cover crops on mycorrhizal fungi have been well documented (Galvez et al, 1995;Boswell et al, 1998;Douds et al, 2005). This study confirmed the potential of warm seasoncover crops in promoting native mycorrhizal fungi in subtropical organic farms.…”
Section: Discussionsupporting
confidence: 77%
“…The beneficial effects of cover crops on mycorrhizal fungi have been well documented (Galvez et al, 1995;Boswell et al, 1998;Douds et al, 2005). This study confirmed the potential of warm seasoncover crops in promoting native mycorrhizal fungi in subtropical organic farms.…”
Section: Discussionsupporting
confidence: 77%
“…Consequently, modern agriculture is in need of alternatives to (i) reduce negative environmental impacts of conventional chemical inputs and (ii) enhance crop production efficiency. One proven biosustainable alternative is naturally occurring arbuscular mycorrhizal (AM) fungi, which are obligate symbionts that establish a mutualistic relationship with most crop plants (33)(34)(35). The fungus receives fixed carbon in the form of hexose from the host root and, in exchange, supplies the root with mineral nutrients, notably phosphorus, zinc, and copper.…”
mentioning
confidence: 99%
“…One of the major constrains for this method is the necessity of large amounts of inoculum, which means the significant inputs for its transportation to the place of use. Thus, it seems to be expedient to utilize the local manufactures of inoculum (Onfarm production) organized in the proximity to final consumers (Douds et al, 2005). In addition, many inoculum producers still develop formulations using different AMF, which are quite often not well characterized in terms of ecological, soil, host or pathogen requirements.…”
Section: Development Of Multi-component Microbial Inoculantsmentioning
confidence: 99%